2016
DOI: 10.1371/journal.pone.0164903
|View full text |Cite
|
Sign up to set email alerts
|

Does the Decline in Caries Prevalence of Latin American and Caribbean Children Continue in the New Century? Evidence from Systematic Review with Meta-Analysis

Abstract: ObjectiveTo carry out a systematic review with meta-analysis of prevalence of caries in Latin America and Caribbean children considering studies performed in this new century.MethodsTwo reviewers searched PubMed, Embase, LILACS and governmental databases through May 2016 to identify papers published in English, Portuguese or Spanish. Studies in those countries performed with 5–6 or 11–13 year-old children and that presented separate prevalence figures from primary and permanent teeth were selected. We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 20 publications
3
71
1
Order By: Relevance
“…However, emerging epidemiological data are showing a worrying trend, with caries experience plateauing or even increasing in some population groups, despite the regular use of fluoride dentifrices in these countries [Agustsdottir et al, 2010;AIHW, 2018;Dye et al, 2017;Haugejorden and Birkeland, 2005]. This raises questions on whether the earlier reduction in caries prevalence rates has continued into this century [Gimenez et al, 2016]. The reported pause in the decline of dental caries has been attributed to the fact that diets across the world are changing to include more processed and sugar-laden foods, limiting the repair potential of fluoride [Duggal et al, 2001].…”
Section: Fluoride -Improving Its Efficacy and Safetymentioning
confidence: 99%
“…However, emerging epidemiological data are showing a worrying trend, with caries experience plateauing or even increasing in some population groups, despite the regular use of fluoride dentifrices in these countries [Agustsdottir et al, 2010;AIHW, 2018;Dye et al, 2017;Haugejorden and Birkeland, 2005]. This raises questions on whether the earlier reduction in caries prevalence rates has continued into this century [Gimenez et al, 2016]. The reported pause in the decline of dental caries has been attributed to the fact that diets across the world are changing to include more processed and sugar-laden foods, limiting the repair potential of fluoride [Duggal et al, 2001].…”
Section: Fluoride -Improving Its Efficacy and Safetymentioning
confidence: 99%
“…However, the latest Global Burden of Disease report revealed that untreated caries in permanent teeth still remains the most common human disease condition worldwide [Kassebaum et al, 2015]. Doubts have also been expressed on whether the earlier decline in caries prevalence has continued into this new century [Gimenez et al, 2016]. Recent caries prevalence studies in the USA and Australia indicate tooth decay may in fact be increasing again [Dye et al, 2007;Chrisopoulos et al, 2016].…”
Section: Caries Epidemiologymentioning
confidence: 99%
“…A recent global report on the burden of oral diseases showed that the prevalence of untreated caries in deciduous teeth remained relatively stable between 1990 and 2015 . Systematic reviews showed that among 5‐6‐ and 11‐13‐year‐old children in Latin American and Caribbean countries, the downward trends in primary teeth previously reported have not continued in the year 2000 …”
Section: Introductionmentioning
confidence: 99%